Aligning Information Technology, Organization, and Strategy 2010
DOI: 10.1007/978-3-8349-8940-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid strategy and firm performance: The moderating role of individual and technological ambidexterity

Abstract: It is discussed whether hybrid strategies are beneficial or detrimental to a firm's performance, because hybrid strategies lead to organizational tensions that arise from the simultaneous pursuit of distinct strategic activities. However, existing studies on the relationship between hybrid strategy and firm performance have largely neglected the role of the organizational architecture. This study tests the hypothesis that an ambidextrous organizational architecture positively moderates the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…It has also been tested on different levels (Chang et al, 2016), such as on the firm level and business unit level (Gibson & Birkinshaw, 2004; Jansen et al, 2012), in projects and teams (Cao et al, 2009; Hirst et al, 2018; Huang & Cummings, 2011; Rosenkopf & Nerkar, 2001; Venugopal et al, 2020), and on the individual level (Lee & Meyer-Doyle, 2017; Mom et al, 2009). Most of the studies showed a positive relationship of organizational ambidexterity with sales growth (Derbyshire, 2014; He & Wong, 2004), transition to scale (Raisch & Tushman, 2016), profitability (Fiss, 2011), return on investment and market share (Hambrick, 1983), and short-term and long-term firm performance (Dolz et al, 2019; Luger et al, 2018; Mahr, 2010; Pertusa-Ortega & Molina-Azorín, 2018; Schmitt & Raisch, 2013; Zimmermann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been tested on different levels (Chang et al, 2016), such as on the firm level and business unit level (Gibson & Birkinshaw, 2004; Jansen et al, 2012), in projects and teams (Cao et al, 2009; Hirst et al, 2018; Huang & Cummings, 2011; Rosenkopf & Nerkar, 2001; Venugopal et al, 2020), and on the individual level (Lee & Meyer-Doyle, 2017; Mom et al, 2009). Most of the studies showed a positive relationship of organizational ambidexterity with sales growth (Derbyshire, 2014; He & Wong, 2004), transition to scale (Raisch & Tushman, 2016), profitability (Fiss, 2011), return on investment and market share (Hambrick, 1983), and short-term and long-term firm performance (Dolz et al, 2019; Luger et al, 2018; Mahr, 2010; Pertusa-Ortega & Molina-Azorín, 2018; Schmitt & Raisch, 2013; Zimmermann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%